Geographic analysis of earthquake damage in Turkey between 1900 and 2012. Issue 6 (1st November 2016) - Gökkaya, Kemal
ABSTRACT: This study investigates the relationship between fatality and magnitude, energy released, time of earthquake occurrence and building damage, and between building damage and magnitude and energy of earthquakes that occurred in Turkey between 1900 and 2012. Patterns of earthquake occurrence and damage are examined across space and time. Ninety-one per cent and eighty-three per cent of the variation in fatality and building damage are accounted for by the energy released from an earthquake, respectively. Building damage explains 85% of the variation in fatality. Seventy-six per cent of the total death toll is a result of the earthquakes that happened between midnight and 5:22 am. There were two significant clusters of earthquakes in Western Turkey between 1955 and 1965 and between 1969 and 1971. Provinces of Erzincan and Kocaeli emerge as hot spots of fatality and building damage. The location of major earthquakes over 112 years tends to parallel the tectonically active areas of Turkey such as the North and East Anatolian Faults and Western Turkey towards the Aegean Sea. Central, central south, extreme north-western, north-eastern and south-eastern Turkey appears to be void of major earthquakes.